The One and the Many Contemporary Collaborative Art in a Global Context - Kester, Grant H. (Duke University Press, 2011)
Collaborative and collective art practices have proliferated around the world over the past fifteen years. In The One and the Many, Grant H. Kester provides an overview of the broader continuum of collaborative art, ranging from the work of artists and groups widely celebrated in the mainstream art world, such as Thomas Hirschhorn, Superflex, Francis Alÿs, and Santiago Sierra, to the less-publicized projects of groups, such as Park Fiction in Hamburg, Networking and Initiatives for Culture and the Arts in Myanmar, Ala Plastica in Argentina, Huit Facettes in Senegal, and Dialogue in central India. The work of these groups often overlaps with the activities of NGOs, activists, and urban planners. Kester argues that these parallels are symptomatic of an important transition in contemporary art practice, as conventional notions of aesthetic autonomy are being redefined and renegotiated. He describes a shift from a concept of art as something envisioned beforehand by the artist and placed before the viewer, to the concept of art as a process of reciprocal creative labor. The One and the Many presents a critical framework that addresses the new forms of agency and identity mobilized by the process of collaborative production
Description based on online resource; title from PDF title page (publisher's Web site, viewed 28. Okt 2020)
Keywords: ART / Criticism; Art -- Philosophy; Artistic collaboration; Creation (Literary, artistic, etc.)